Research on the ratio of multicomponent emulsion flooding system - Zhiqiang, Man; Wenxiang, Wu (Frontiers in Energy Research, 2023)
In recent years, field test and industrialized application of ASP (alkaline/ surfactant/ polymer) flooding has been carried out in oilfields , which has obtained an obvious effect on increasing oil and decreasing water and good economic efficiency.However, due to the large proportion of alkali in the ASP flooding system, there are problems such as severe scaling and high cost during field tests, which restrict the promotion of ASP flooding.In order to reduce the amount of alkali used, achieve the goal of reducing scaling and costs, and meanwhile improve emulsification performance while maintaining interfacial activity, a multicomponent emulsion flooding system was developed by combining emulsifier HEFR2 with petroleum sulfonate and sacrificial agent LSCP1 with NaOH.Through laboratory experiments, the water extraction rate, particle diameter, Tsi value, and interfacial activity of the multicomponent emulsion flooding system were tested under different conditions.The results show that when the mass ratio of petroleum sulfonate to emulsifier HEFR2 is between 3:1 and 5:1, and the mass ratio of sacrificial agent LSCP1 to NaOH is between 3:1 and 7:1, the multicomponent emulsion flooding system can maintain good emulsification stability and interfacial activity.The multicomponent emulsion flooding system significantly reduces the amount of alkali used, and the cost of chemical agents is 11% lower than that of the ASP flooding system. At the same time, it achieves the goal of improving the stability of emulsifiers, maintains interfacial activity and reduces costs. This technology has broad application prospects.